Adolf Bierbrauer. - Kolbe, Veronika; Leyer-Pritzkow, Martin; Mösl, Roswitha; Reuter, Helmut ([S.l.] : Martin Leyer-Pritzkow, 1999)
Adolf Bierbrauer is an artist who has avoided the public eye for 65 years.He and his work are now introduced to a broad public for the first time. Especially impressive are his Hypnosis Paintings from the early 50s and the Somnambulic Paintings, which he has created in recent years . The artistic work of Bierbrauer, a painter who is today 84 years old, was developped apart from any contemporary artistic trends. Now, for the first time, Bierbrauer allows a glimpse of his artistic creations. A work with a unique personality comes into view, a work which has always had the human being at its center. His early works, such as portraits and nudes, were pure representations of people. In the course of his career as an artist, doctor, and psychotherapist, however, he has come even nearer to the hidden contents of the human psyche. Bierbrauer painted the Hypsnosis Paintings, from the description of images which appeared to his patients while they were in a trance-like condition. The Somnambulic Paintings call to mind works of the Art brut and of Tachism. They are to be interpreted as messages from the hidden regions of the soul. In his latest works, Bierbrauer has completely separated himself from anything comparable in art history. He developed a cryptic symbolic language, which includes abstract medium, symbols and writings.
biog. p.161-164
Duits
Engels
boek
Keywords: Bierbrauer, Adolf